2015
DOI: 10.1080/00220973.2014.963214
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Text Complexity as Characterized by Readability and Cohesion

Abstract: To better understand dimensions of text complexity and their effect on the comprehension of adolescents, 103 high school seniors were randomly assigned to 4 groups. Each group read versions of the same 2 informational passages and answered comprehension test items targeting factual recall and inferences of causal content. Group A passages had a challenging readability level and high cohesion; Group B passages had an easier readability and low cohesion; Group C passages had a challenging readability level and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In addition, teachers should consider whether the text will motivate and engage students by containing elements of cultural relevancy, offering different perspectives on issues, or making connections to real-world events (Leko, Mundy, Kang, & Datar, 2013). Although it may be tempting to use a readability level as the indicator of a text’s appropriateness, readability alone does not fully capture the complexity of a text (Reed & Kershaw-Herrera, 2016; Lupo, Tortorelli, Invernizzi, Ryoo, & Strong, 2019). Rather, teachers need to combine quantitative indicators of a text’s difficulty with qualitative indicators, such as the demands that the text places on students’ background knowledge, the density of the information presented, and the use of abstract or figurative language (Pearson & Hiebert, 2013).…”
Section: Text Structure Instruction With Authentic Textsmentioning
confidence: 99%
“…In addition, teachers should consider whether the text will motivate and engage students by containing elements of cultural relevancy, offering different perspectives on issues, or making connections to real-world events (Leko, Mundy, Kang, & Datar, 2013). Although it may be tempting to use a readability level as the indicator of a text’s appropriateness, readability alone does not fully capture the complexity of a text (Reed & Kershaw-Herrera, 2016; Lupo, Tortorelli, Invernizzi, Ryoo, & Strong, 2019). Rather, teachers need to combine quantitative indicators of a text’s difficulty with qualitative indicators, such as the demands that the text places on students’ background knowledge, the density of the information presented, and the use of abstract or figurative language (Pearson & Hiebert, 2013).…”
Section: Text Structure Instruction With Authentic Textsmentioning
confidence: 99%
“…Like newer calculators used to assess the difficulty of texts (e.g., Coh‐Metrix, TextEvaluator), readability measures privilege these features equally rather than identifying the interaction between features that actually make a text difficult. For example, less cohesive texts are harder to read for students with minimal background knowledge on a topic (Reed & Kershaw‐Herrera, ). Readers with high knowledge on a topic are able to generate more inferences when reading less cohesive texts (McNamara, Ozuru, & Floyd, ).…”
Section: Misconceptions About Reading Difficult Textsmentioning
confidence: 99%
“…At the high school level, Reed and Kershaw-Herrera (2016) had Spanish L1 speaking seniors read several informational texts and answer comprehension questions about them. They found that readability and textual cohesion influenced these secondary English L2 learners' reading comprehension.…”
Section: Empirical Research On Readability and Understandabilitymentioning
confidence: 99%